2021
DOI: 10.31557/apjcp.2021.22.11.3513
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Evaluation of Circulating MiR-106a and Raf-1 as Breast Cancer Diagnostic and Prognostic Markers

Abstract: Objective: MicroRNAs (MiRNAs) regulate mammalian cell growth, differentiation, and apoptosis by altering the expression of other genes and serve multiple roles in tumorigenesis and progression. Proto-oncogene serine/threonineprotein kinase (RAF-1) functions as a part of the MAPK/ERK signal transduction pathway. The present study aim was to prospectively evaluate MicroRNA 106a (MiR-106a) and RAF-1 as a diagnostic and prognostic factor in early prediction of breast cancer (BC), recurrence and early detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Altogether, it was reported that miR-106a could contribute to enhanced cell proliferation due to lowered sensitivity to chemotherapeutic agents [69,102]. Another study revealed a possible correlation between miR-106a levels and breast cancer cell proliferation mediated by RAF-1, activating the MAPK/ERK signaling pathway [68].…”
Section: Mir-106amentioning
confidence: 97%
See 1 more Smart Citation
“…Altogether, it was reported that miR-106a could contribute to enhanced cell proliferation due to lowered sensitivity to chemotherapeutic agents [69,102]. Another study revealed a possible correlation between miR-106a levels and breast cancer cell proliferation mediated by RAF-1, activating the MAPK/ERK signaling pathway [68].…”
Section: Mir-106amentioning
confidence: 97%
“…The candidates were selected based on the latest reports indicating the role of miRNA in breast cancer. Consequently, a broad analysis of selected miRNA targets suggested some good candidate markers based on the global data at TargetScanHuman Induction of EMT and gemcitabine resistance [63] PI3K/Akt, MEK/ERK [58] Activation PI3K/Akt and MEK/ERK signaling pathways [58] Development of MDR [58] TPM1, TGF-β [64] Repression of expression TPM1 [65,66] Increased BC cells proliferation, migration, invasion, survival, and EMT [64] Mesenchymal cell markers (N-cadherin, Vimentin, α-SMA) [67] Activation of mesenchymal cell markers [67] Re-expression of miR-21 is responsible for migration and invasion by activating the EMT process in MCF7 cells [67] Epithelial cell marker (E-cadherin) [67] Inhibition of epithelial cell marker [67] miR-106a Upregulated Serum, qRT-PCR [68] Bcl-2,ABCG2, BAX, P53, RUNX3 [69] Upregulation of Bcl-2 protein and multidrug transporter ABCG2. Downregulation of BAX protein and genes products: P53, RUNX3 [69] Promotes BC cells proliferation and invasion [69] * Inhibition of miR-106a downregulates the expression of Bcl-2, ABCG2 and upregulates the BAX, P53, RUNX3 expression [69] RAF-1 [68] Decreases RAF-1 levels and RAF-1 is a part of MAPK/ERK signaling pathway [68] Possibly induces proliferation and decreases apoptosis in BC cells through regulation of the MAPK/ERK signaling pathway, which controls gene expression [68] ZBTB4 [70][71][72] Negative regulation of ZBTB4 gene, which functions as a tumor suppressor gene [70][71][72] * Restoration of ZBTB4 suppress Sp1, Sp3, Sp4 expression resulting in inhibition of BC cells proliferation, invasion [70][71][72] miR-155 Upregulated Serum, qRT-PCR [73] TERF1 [74] Reduction in the...…”
Section: Microrna Profilingmentioning
confidence: 99%
“…Another player in BC etiopathogenesis is miR-106a, which promotes cancer progression through the downregulation of RAF-1 [ 69 ], P53 , BAX , and RUNX3 and the upregulation of Bcl-2 and ABCG2 ; it also confers cisplatin resistance upon its upregulation [ 70 , 71 ].…”
Section: Epigenetics Of Bc and The Role Of Mir-125mentioning
confidence: 99%
“…On the contrary, the level of circulating miRNAs is helpful to classify BC based on the clinical and histopathological grading [ 47 , 48 ]. For instance, the increased levels of exosomal miR-363-5p [ 25 ] and circulating miR-106a levels [ 49 ] were useful to differentiate BC with and without lymph node involvement. A clinical study reported that the elevation of four serum miRNAs, including miR-16-5p, miR-17-3p, miR-451a and miR-940, was observed in metastatic BC as compared to local, non-metastatic BC [ 50 ] and downregulation of plasma miR-195 level was also observed in metastatic BC [ 51 ].…”
Section: Current Trends and Research Outcomes Of Circulating Mirna As...mentioning
confidence: 99%